Розробка модуля «аналіз продажів» іс «оптбуд» - Вінницька. Є. А. (ХНУРЕ, 2023)
This article highlights the importance of conducting various methods of analyses to improve a company's efficiency and productivity. It proposes a solution that combines some of the analysis methods, including sales dynamics analysis, ABC analysis, control analysis of sales volume, sales analysis, and customer analysis. The proposed solution is aimed at providing the company with a more detailed view of its processes and will be presented in a user-friendly form.